Використання систем електронного документообігу в міській раді - Вакуліч, Марія; Марковець, Олександр (Видавництво Львівської політехніки, 2020)
The article presents the basic electronic workflow services used in the city council. Their main advantage is the convenience and speed of electronic document exchange.
Keywords: електронний документообіг; система електронного документообігу; електронний документ